Impact of the natural filler babassu on the processing and properties of PBAT/PHB films. (September 2019) - Hoffmann, R.; Morais, D.D.S.; Braz, C.J.F.; Haag, K.; Wellen, R.M.R.; Canedo, E.L.; de Carvalho, L.H.; Koschek, K.
Abstract: Melt extruded films consisting of polybutyrate adipate terephthalate (PBAT), poly(3-hydroxybutyrate) (PHB) and babassu as a natural and cost-effective filler were studied aiming at the preparation of partly bio-based and biodegradable films. PHB suffers from low thermal stability entailing a narrow processing window. Rheological, thermal and mechanical properties revealed that an effective processing of the PBAT/PHB blends with well-dispersed babassu is possible. Thermal degradation of the composites during processing and the mechanical properties are driven mainly by the polymer composition and less by the filler. However, babassu addition reduces the crystallization rate and facilitates by this the handling of the extruded films prior to solidification. Among the composites investigated, the composites based on 50%PBAT/50%PHB blends combined both, best processing and handling parameters as well as thermal and mechanical material properties. Babassu was found to facilitate PHB processing while maintaining the overall mechanical properties and giving access to ecologically friendly, cost-effective composite materials.